Peran Kepempinan Kepala Sekolah di Era Revolusi Industri 4.0 dalam Meningkatkan Mutu SMP Negeri 2 Alasa Kabupaten Nias Utara - F. Viktor Zebua; Mangampu Hasintongan Panjaitan; Fa’amoi Daeli; Hotden Leonardo Nainggolan; Tongam Sihol Nababan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The study aims to describe the role of the principal: 1) as an educator and as a manager; 2) as an administrator and supervisor; 3) as a leader, innovator and motivator; 4) analyzing leadership styles and supporting and inhibiting factors in achieving results. The research was conducted at SMP Negeri 2 Alasa, District of North Nias, using a qualitative and qualitative approach. The data used are primary and secondary data. Data collection techniques with interviews, observation, and documentation. The results showed: 1) the role of the principal as an educator can improve the professionalism of educators; 2) the role of the principal as a manager can manage and solve problems; 3) the role of the principal as an administrator can manage school administrative activities; 4) the role of the principal as a supervisor can oversee supervision activities; 5) the role of the principal as a leader is to communicate and create conducive conditions; 6) the role of the principal as an innovator can develop learning and create programs; 7) the role of the principal as a motivator, namely providing motivation to educators and students with a democratic leadership style, 8) supporting factors, namely human resources in this case educators and students, infrastructure and support provided by the guardians of students, while the inhibiting factor is the instability of internet power.